Assessing the Motivations of Nursing Students Graduated from Non-STEM SHS Strands to Pursue BSN - Alcomendas, Julian Grayfrex; Drexel Heinz (MALATA SAINS INDONESIA, 2025)
Introduction: Previous studies on nursing career choice commonly emphasize interest in healthcare, job security, and social influence; however, limited literature explores why non-STEM Senior High School graduates pursue the Bachelor of Science in Nursing (BSN), particularly in the Philippine context. Objective: This study aims to contribute to the knowledge base of the nursing profession and catalyze or help develop positive changes and improvements in different sectors. Methods: This quantitative descriptive-correlational study examined the factors influencing BSN students who did not graduate from STEM strands in Senior High School to pursue a nursing career, guided by the Theory of Planned Behavior (TPB). Using purposive non-random sampling, 105 participants completed a survey assessing career opportunities and job safety, interest in healthcare, family and peer influence, perceived prestige, institutional characteristics, and selected demographic variables. Data were analyzed using descriptive statistics, one-way analysis of variance, and multiple regression analysis. Results: Career opportunities and job safety (M = 3.36) and perceived prestige and societal expectations (M = 3.26) were strongly influential in career choice. Interest in healthcare (M = 2.98) and institutional characteristics (M = 2.94) were influential, whereas family and peer influence (M = 2.42) was not. TPB assessment showed a very positive attitude toward BSN (M = 3.55), moderate parental influence (M = 2.97), and moderate perceived behavioral control (M = 2.95). Demographic variables were not significantly associated with any factor. Among TPB constructs, attitude, parental subjective norms, and perceived behavioral control significantly influenced career choice. Conclusion: The study concludes that non-STEM students’ motivation to pursue BSN is driven primarily by career-related considerations rather than social influence or prior academic alignment.